The influenza virus M2 protein cytoplasmic tail interacts with the M1 protein and influences virus assembly at the site of virus budding - Chen, Benjamin J; Leser, George P; Jackson, David; Lamb, Robert A (Journal of virology, 2008)
The cytoplasmic tail of the influenza A virus M2 proton-selective ion channel has been shown to be important for virus replication. Previous analysis of M2 cytoplasmic tail truncation mutants demonstrated a defect in incorporation of viral RNA (vRNA) into virions, suggesting a role for M2 in the recruitment of M1-vRNA complexes. To further characterize the effect of the M2 cytoplasmic tail mutations on virus assembly and budding, we constructed a series of alanine substitution mutants of M2 with mutations in the cytoplasmic tail, from residues 71 to 97. Mutant proteins M2-Mut1 and M2-Mut2, with mutations of residues 71 to 73 and 74 to 76, respectively, appeared to have the greatest effect on virus-like particle and virus budding, showing a defect in M1 incorporation. Mutant viruses containing M2-Mut1 and M2-Mut2 failed to replicate in multistep growth analyses on wild-type (wt) MDCK cells and were able to form plaques only on MDCK cells stably expressing wt M2 protein. Compared to wt M2 protein, M2-Mut1 and M2-Mut2 were unable to efficiently coimmunoprecipitate with M1. Furthermore, statistical analysis of planar sheets of membrane from cells infected by virus containing M2-Mut1 revealed a reduction in M1-hemagglutinin (HA) and M2-HA clustering as well as a severe loss of clustering between M1 and M2. These results suggest an essential, direct interaction between the cytoplasmic tail of M2 and M1 that promotes the recruitment of the internal viral proteins and vRNA to the plasma membrane for efficient virus assembly to occur.